Organochlorine - Nuro, Aurel (IntechOpen, 2018)
Organochlorines (OC) are organic molecules with chlorine in their structure. There is a large number of organochlorine compounds known. Large amounts of chlorinated organic compounds are produced for industrial, agricultural, pharmaceutical, household purposes, etc. In many studies, the main focus is on OC that have been evaluated as environmental contaminants with toxic effects on humans. Different types of organochlorines have been produced throughout the world. Some of the most popular classes are organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), dioxins, chlorobenzenes, chlorophenols, chlorinated alkanes, etc. Organochlorine compounds are very stable. Generally, they are molecules of moderate polarity (low solubility in water). This makes OCs easily soluble in fats. They are found in almost all environments: air, water, soil, sediments and biota samples. They can spread out easily in different geographic altitudes and latitudes. Volatile and semi-volatile OCs have the ability to travel far distances from the place where they were used. Some studies have reported some organochlorines in the North Pole at the same levels as the areas where they were produced or applied. They have the ability to bioaccumulate easily in biota. Passing through the food chain levels, they increase their concentrations (biomagnifying). The main access pathways for OCs to the human body are through foods and exposures. Generally, they display their effects after a relatively long period of exposure. This is the main reason why they were produced and used for a long time before their production and use was banned. The most important health effects that organochlorines can cause are: mutagenic, endocrine-disruptor, carcinogenic and central nervous or peripheral disorders. After identification of the consequences, production of OCs and use was banned in many countries but their effects are still being seen many years later.